2011
DOI: 10.1186/1743-422x-8-299
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the transcripts of human cytomegalovirus UL144

Abstract: BackgroundThe genome of human cytomegalovirus (HCMV) has been studied extensively, particularly in the UL/b' region. In this study, transcripts of one of the UL/b' genes, UL144, were identified in 3 HCMV isolates obtained from urine samples of congenitally infected infants.MethodsNorthern blot hybridization, cDNA library screening, and RACE-PCR were used.ResultsWe identified at least 4 differentially regulated 3'-coterminal transcripts of UL144 in infected cells of 1,300, 1,600, 1,700, and 3,500 nucleotides (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Qi et al [2011] have identified the transcripts of the UL138-UL145 region as two large families of polycistronic transcripts, with the UL145 gene representing one component of the second family. He et al [2011] have confirmed that UL144 and UL145 are expressed as a polycistron. In the current study, two abundant clusters of UL145 transcripts in H, C, and X clinical isolates were detected by Northern blot in late kinetics.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Qi et al [2011] have identified the transcripts of the UL138-UL145 region as two large families of polycistronic transcripts, with the UL145 gene representing one component of the second family. He et al [2011] have confirmed that UL144 and UL145 are expressed as a polycistron. In the current study, two abundant clusters of UL145 transcripts in H, C, and X clinical isolates were detected by Northern blot in late kinetics.…”
Section: Discussionsupporting
confidence: 77%
“…Although the bands were smeared in a narrow area, the size of the transcripts was similar in the three strains isolated from patients. The cluster of transcripts between 1,400 and 1,600 nt in the Northern blot should represent transcripts from the polycistron of UL144 and UL145 identified by He et al [2011]. However, one monocistron only containing the sequence of the UL145 ORF was confirmed in the present study by several evidences, including the results of cDNA library screening, Northern blot and RACE.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…UL144 is expressed early in HCMV infection with protein detected four hours post-infection . Transcription from the UL144 gene is complex, with at least four differentially regulated transcripts expressed (He et al, 2011). One of these transcripts encompasses UL142 through UL145, and all transcripts contain both UL144 and UL145.…”
Section: Gene Structure and Expressionmentioning
confidence: 99%